Psychosocial disadvantage and residential remoteness is associated with Aboriginal women’s mental health prior to childbirth - Bhat, Sunil Kumar; Marriott, Rhonda; Galbally, Megan; Shepherd, Carrington CJ (International Journal of Population Data Science, 2020)
Introduction Optimal mental health in the pre-conception, pregnancy and postpartum periods is important for both maternal and infant wellbeing. Few studies, however, have focused on Indigenous women and the specific risk and protective factors that may prompt vulnerability to perinatal mental disorders in this culturally diverse population. Objectives To assess mental health contacts in the period before childbirth among Australian Aboriginal and Torres Strait Islander women, the association with socioeconomic factors and whether it differs by geographic remoteness. Methods This is a retrospective cohort study of 19,165 Aboriginal mothers and includes all Aboriginal mothers and their children born in Western Australia from January 1990 to March 2015. It draws on population-level, linked administrative data from hospitals and mental health services, with a primary focus on the mental health contacts of Aboriginal women in the 5 years leading up to childbirth. Results The prevalence of maternal mental health contacts in the five years prior to birth was 27.6% (93.6% having a single mental health disorder), with a greater likelihood of contact in metropolitan areas compared with regional and remote settings. There was a positive relationship between socioeconomic advantage and the likelihood of a mental health contact for women in metropolitan (β = 0.044, p=0.003) and inner regional areas (β = 0.033, p=0.018), and a negative association in outer regional (β = -0.038, p=0.022), remote (β = -0.019, p=0.241) and very remote regions (β = -0.053, p<0.001). Conclusions The findings from this study provide new insights on the dynamic relationship between SES, geographic location and mental health issues among Aboriginal women in the five years leading up to childbirth. The results underscore the need to apply location-specific approaches to addressing the material and psychosocial pathways that lead to mental health problems and the provision of culturally safe, appropriate and accessible services for Aboriginal women.